Respon Berbagai Jenis Kotoran Ternak Sebagai Media Tumbuh Terhadap Densitas Populasi Maggot (Hermetia illucens) - H Herlinae; Y Yemima; Lista Ariatie Kadie (Fakultas Peternakan Universitas Kristen Palangka Raya, 2021)
The aim of this research were to know the effect of various types of livestock manure as maggot growing media on maggot population density and to know various types of livestock manure as maggot growing media that can provide the best results on maggot population density. The study was conducted using a Randomized Block Design Method with 4 treatments with 5 replications as a group, A = broiler manure 50% + tofu waste 50%, B = laying hens manure 50% + tofu waste 50%, C = manure pork 50% + tofu waste 50% and D = 50% cow manure + 50% tofu waste. The result of this study is that various types of livestock manure as maggot growing media have no effect on the maggot population density. Keywords : Livestock manure, maggot, population density.